Developing ESP E-Module Course Design Based on Canva for Law Students - Rini Dwi Septiyani; Iron Fajrul Aslami; Dewi Surani (Jurusan Manajemen Pendidikan Islam Fakultas Tarbiyah dan Keguruan UIN Sultan Maulana Hasanuddin Banten, 2022)
This research aims to design and develop an e-module based on the Canva application, and to measure the validity of e-modules for legal English courses. This research uses Research and Development (R&D) research with the ADDIE model with five stages: first is analyzing problems, potentials, and needs. The second is designing to determine a Canva Digital application used, the design/theme of the e-module, and the format. The third stage is developing the design that has been previously designed by being developed through the Canva Digital application. In addition, at this stage, a validation test is carried out for the validators, namely material experts, linguists, and media experts to determine the feasibility of the E Module that has been designed and developed. The fourth stage is Implementation. In this stage, a practicality test and effectiveness test are carried out on law students of Bina Bangsa University. The final stage is evaluation, at this evaluation stage, is the stage of implementing digital Canva-based E-Module improvements that have been given input by material experts, linguists, and media experts. Quantitative and qualitative data were employed to collect the information. The finding reveals the average score for eligibility assessment results is 91,79 %, the average score for practicality assessment results is 91,86 %, and the average score for effectiveness is 84,66. In conclusion, the eligibility assessment is classified as